A Study on the Use of Speech Acts and the Levels of Trustworthiness in Investigative Interviews - Firqo Amelia; Ahmad Yusuf Firdaus; Sufil Lailiyah (Pioneer: Journal of Language and Literature, 2018)
This article studies the relationship between the types of speech acts and the level of trustworthiness provided by the interviewees in the process of investigative interviewes in Situbondo police office. The types of speech acts were analyzed based on Searle’s illocutionary acts, i.e. assertives, commissives, directives, expressives, and declarations. While the level of trustworthiness was analyzed using three levels of trustworthiness, i.e. high, moderate, and low. This is a qualitative research. The data in the form of interviewees’ speech and assessment of the level of trustworthiness were collected using sampling technique method, content analysis, and interview. The results of this study indicate that the five types of speech acts can be found in the interviewee’s statements in investigation process at Situbondo resort police station. The type of assertive speech acts that serves to convey information was the most frequently used by the interviewees in answering investigator questions. This is because the questions of the investigator aims to gather information about a crime. In addition, this study also found that expressive speech acts tended to produce speech with low level of trustworthiness, while assertives tended to produce speech with moderate levels of trustworthiness.